2000
DOI: 10.1021/jp9937611
|View full text |Cite
|
Sign up to set email alerts
|

Kinetically Controlled Growth of Helical and Zigzag Shapes of Carbon Nanotubes

Abstract: This paper focuses on the growth mechanism of the multiwalled carbon nanotubes exhibiting helical and zigzag growth morphologies. Our data support a kinetically controlled growth model in which the creation rates of the pentagon and heptagon carbon rings determine the geometrical shapes of the nanotubes. The carbon nanotube is believed to be grown from a carbon cluster that is nucleated from a pentagon carbon ring followed by a spiral shell growth. The pairing of pentagonal-heptagonal (P-H) carbon rings is ess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
74
0
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(76 citation statements)
references
References 18 publications
1
74
0
1
Order By: Relevance
“…They show promise as components of nanoelectronic devices, field-emission displays, and high-strength composites. MWNTs are usually fairly straight, but under some growth conditions, tubes form with a corkscrew shape (2)(3)(4). The tubes grow out of molten catalyst particles that have been supersaturated with carbon, and the corkscrew shape arises when there is a nonuniform rate of deposition of carbon around the circumference of the tube (5).…”
Section: Kinksmentioning
confidence: 99%
“…They show promise as components of nanoelectronic devices, field-emission displays, and high-strength composites. MWNTs are usually fairly straight, but under some growth conditions, tubes form with a corkscrew shape (2)(3)(4). The tubes grow out of molten catalyst particles that have been supersaturated with carbon, and the corkscrew shape arises when there is a nonuniform rate of deposition of carbon around the circumference of the tube (5).…”
Section: Kinksmentioning
confidence: 99%
“…[17,18] Patterned growth of coiled nanotubes based on using previously aligned straight CNTs as templates was also demonstrated. [19] It is typically found that such methods, in addition to limiting the amount of material due to the catalyst distribution, is often accompanied by the formation of linear multiwalled nanotubes.…”
mentioning
confidence: 99%
“…Other formation mechanisms invoke localized stresses and anisotropic rates of carbon deposition [19,24] on faceted catalyst particles. [17] However, there is no experimental evidence for the above, as it is seen that helical structure is induced even though catalyst particles are not obviously present in the structure. It is also noted that the above mechanisms cannot be invoked for amorphous carbon nanocoils [16] and compound (e.g., boron carbide) nanowires.…”
mentioning
confidence: 99%
“…However, so far all experimental observations have been made on coiled multiwalled CNTs and noncrystalline carbon nanofibers ͑CNFs͒, and it is difficult to imagine the conditions necessary for the uniform and periodic introduction of the P-H pairs 18 in such structures. The most widely accepted models for coiling, in NTs, are then related to ͑a͒ the anisotropic rates of carbon deposition and/or ͑b͒ nature and geometry of the catalyst particle.…”
Section: Introductionmentioning
confidence: 99%
“…21 Neither of these models makes any predictions nor gives specific reasons for helical growth, maintaining that "rather special conditions" 21 would be needed for coiling. However, the faceting of the catalyst particle has never been explicitly shown, and coiled tubules have also been obtained where catalyst particles are either not present anywhere in the nanostructure or have been found, through high resolution transmission electron microscopy ͑TEM͒, to be embedded 18 in the CNT. The above models also cannot explain the synthesis of amorphous carbon nanocoils 22 or compound ͑e.g., Boron Carbide͒ nanowires.…”
Section: Introductionmentioning
confidence: 99%